The Geisha coffee variety and its status in the world and in Mexico - Silva Rincon, Cristina Ione; Alarcón Gutiérrez, Enrique; García Pérez, José Antonio; Sánchez-Velásquez, Lázaro Rafael; Iglesias Andreu, Lourdes Georgina (Revista Mexicana de Ciencias Agrícolas, 2024)
The Geisha coffee variety belongs to the species Coffea arabica; L.1753; it has the potential to replace traditional varieties due to its partial resistance to rust and high cup quality. Although information about it is scattered, this work reviews and compiles its morphological, productive, environmental, and historical characteristics and current situation in the world and in Mexico. Information search included scientific papers, books, and digital theses available online. As a result, it was found that Geisha, native to Ethiopia, has S-shaped branches, reaches over 3 m in height and faces threats such as the coffee berry borer (Hypothenemus hampei Ferrari 1867), the leaf miner (Leucoptera coffeella; Guérin-Méneville and Perrrottet, 1842), and the root mealybug (Planococcus lilacinus; Cockerell, 1905). Its partial resistance to rust, thanks to the SH1 and SH5 genes, gives it advantages against coffee rust (Hemileia vastatrix; Berkeley and Broome, 1869). Recognized for its exceptional quality (95.25/100), it has reached prices of up to 1 029 dollars per pound, generating global interest. In conclusion, Geisha arrived in Mexico in 1980 through the Mexican Coffee Institute; however, its production in the country is limited, with presence in certified farms and for local consumption. This review fulfils the objective of highlighting its characteristics in Mexico and in other parts of the world.